Ideology and Distortions of the Entrepreneurial Concept. The Results of Conflict in Organizational Culture - Vlasov, Petro; Kiseleva, Anna (International Journal of Emerging Trends in Social Sciences, 2017)
Organizations constantly exist in a process of sense-making, interpretation and sense-transfer. It is initiated by various centers (top-managers, external organizational environment, clients). The initial concept of organization is being distorted repeatedly. The initiator’s initial concept loses its symbolic value and can’t be realized. Managers avoid to produce and transmit meanings, refuse to reduce uncertainty. They reduce the pressure of responsibility through ideology, creating the discourse that justifies such behavior. The function of ideology is to simplify, depersonify and to reduce the need for productive tension. They start to compete with initiator for the meaning, creating organizational myth. Consequently, official organizational policy must first of all be oriented towards transformation of ideology into methodology of solving organizational problems.